2003
DOI: 10.4309/jgi.2003.9.5
|View full text |Cite
|
Sign up to set email alerts
|

Instant-win products and prize draws: Are these forms of gambling?

Abstract: Instant-win marketing and prize draws are not particularly new but many companies (particularly in the U.K.) appear to be aiming them at younger age groups. This brief paper argues that some children appear to "chase" their losses on instant-win products in the same way a gambler chases losses, and that they are a form of adolescent gambling or, at the least, a gambling precursor. This paper also briefly overviews the prize draw culture in the U.K. Policy recommendations for both instant-win and prize draw pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Such a young start is disturbing because researchers have also shown that the earlier a person starts gambling, the more likely it is that he or she will develop problematic gambling behavior (Fisher, 1993; Griffiths, 2003; Gupta & Derevensky, 1998; Huxley & Carroll, 1992; Winters et al., 1993). It is intuitive that if a person with some degree of predisposition to addiction is exposed to an addicting agent at a more vulnerable time (an earlier age), that person will be more likely to develop a full‐blown addiction.…”
mentioning
confidence: 99%
“…Such a young start is disturbing because researchers have also shown that the earlier a person starts gambling, the more likely it is that he or she will develop problematic gambling behavior (Fisher, 1993; Griffiths, 2003; Gupta & Derevensky, 1998; Huxley & Carroll, 1992; Winters et al., 1993). It is intuitive that if a person with some degree of predisposition to addiction is exposed to an addicting agent at a more vulnerable time (an earlier age), that person will be more likely to develop a full‐blown addiction.…”
mentioning
confidence: 99%